The Effect of Good Corporate Governance and Corporate Social Responsibility on Financial Performance with Earning Management as an Intervening Variable - Munandiroh, Luluk Hasanatul; Nabila, Rifda; Afina, Khoirun Nissa (Journal of Accounting Inquiry, 2025)
Purpose: This study examines the influence of Good Corporate Governance (GCG) and Corporate Social Responsibility (CSR) on financial performance, with earnings management as an intervening variable. It provides alternative empirical evidence within the regulatory context of sharia-compliant firms. Methodology: A quantitative approach with panel data is employed. Secondary data were obtained from audited annual reports and sustainability disclosures published on company websites and the Indonesia Stock Exchange (idx.co.id). Purposive sampling identified 23 consumer goods companies listed on the Indonesian Sharia Stock Index (ISSI) for 2020–2023. Findings: The results indicate that GCG has a negative and significant effect on financial performance, suggesting compliance costs or reduced managerial flexibility. CSR shows no effect on financial performance, implying that disclosures in ISSI firms may be symbolic. GCG positively and significantly influences earnings management, while CSR does not. Earnings management has a negative and significant effect on financial performance. Moreover, earnings management does not mediate the relationship between GCG or CSR and financial performance. Novelty: This study focuses on sharia-compliant consumer goods companies listed on ISSI, an institutional context emphasizing ethical governance, transparency, and restrictions on speculative activities. These requirements may generate distinct behavioral patterns in governance, CSR practices, and earnings manipulation, offering insights into how GCG, CSR, and earnings management interact within an ethics-based governance framework.